Guía educomunicativa para fomentar la lectura de las obras ecuatorianas: cuentos en jóvenes. Caso Colegio Liceo del Sur - Reyes Donoso, Andrea Johanna (2015)
The present work aims to promote the reading of Ecuadorian works in young people, through the story, which has its own identity by the harmony that exists between the characters and the locations, the manner in which the character denotes factors that qualify him/her as Ecuadorian, and personality that the author gives the character that is marked on purpose. Later this is what is the communication and the important concepts that contribute to the reading within and outside of the educational establishments, fostering the love toward her through stories that bring us closer to the reality; providing knowledge and lessons learned through experiences, adventures, imagination and feelings of the author. Understanding to the reading and communication as inseparable concepts, a comparison is made to keep it clear that the world of letters enriches the thought and life, as well as writing and spelling that has always been important and valuable at the time of writing. In this way, the young people may realize that reading should not be an obligation but a personal decision enriching in every aspect; this activity provides many benefits in areas related to communication and the way we see the world and live the day to day, involving the mind where the knowledge is archived and where are added new; at the same time, which is opening and importance to the works that deal with Ecuadorian realities close to us.